2011
DOI: 10.1021/jp202223b
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Alkaline Fading of Phenolphthalein in Microemulsions

Abstract: The reactions of the alkaline fading of phenolphthalein (PN) have been studied in water/sodium bis(2-ethylhexyl)sulfosuccinate (AOT)/isooctane microemulsions by monitoring the absorbance changes of PN in the system with the time and the results compared with those found for the same reactions in aqueous solutions. It was found that the values of the equilibrium constants and the forward reaction rate constants in the microemulsions were significantly larger than that in aqueous solutions and decreased with inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 30 publications
0
31
0
Order By: Relevance
“…The values of k and K at various temperatures with their estimated uncertainties are listed inTable I. It was found that the observed rate constant of the alkaline fading of PN in (2BE + PN) aqueous solution was about 2.0 × 10 −3 mol l −1 s −1 at 298.15 K, two times smaller than that in the aqueous medium determined in our previous work 26. …”
mentioning
confidence: 75%
See 2 more Smart Citations
“…The values of k and K at various temperatures with their estimated uncertainties are listed inTable I. It was found that the observed rate constant of the alkaline fading of PN in (2BE + PN) aqueous solution was about 2.0 × 10 −3 mol l −1 s −1 at 298.15 K, two times smaller than that in the aqueous medium determined in our previous work 26. …”
mentioning
confidence: 75%
“…The reaction of alkaline fading of PN may be de- 26 where L 2− is red-pink quinonoid and LOH 3− is colorless carbinol. The reaction becomes a pseudo-first-order reaction with respect to L 2− when the concentration of OH − was much higher than that of L 2− .…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…There is growing interest in recent times on the influence of different surfactants on the kinetics and mechanism of different reactions . Reaction rates are often modified owing to hydrophobic and/or electrostatic interactions between the reactant species and surfactant monomers or micelles.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical reactions rates are changed in the presence of self‐organized assemblies such as micelles . Effects of surfactant molecules and their micelles on these reactions can be attributed to their electrostatic and hydrophobic interactions with reactants.…”
Section: Introductionmentioning
confidence: 99%